Short Telomeres, but Not Telomere Attrition Rates, Are Associated With Carotid Atherosclerosis - Toupance, Simon; Labat, Carlos; Temmar, Mohamed; Rossignol, Patrick; Kimura, Masayuki; Aviv, Abraham; Benetos, Athanase (Hypertension (Dallas, Tex. 1979), 2017)
Short telomeres are associated with atherosclerosis. However, the temporal relationship between atherosclerosis and telomere length is unclear. The objective of this work was to examine the temporal formation and progression of carotid atherosclerotic plaques in relation to telomere dynamics. In a longitudinal study, comprising 154 French men and women (aged 31–76 years at baseline), carotid plaques were quantified by echography, and telomere length on leucocytes was measured by Southern blots at baseline and follow-up examinations. Telomere attrition rates during the 9.5-year follow-up period were not different in individuals with plaques at both baseline and follow-up examinations (23.3±2.0 base pairs/y) than in individuals who developed plaques during the follow-up period (26.5±2.0 base pairs/y) and those without plaques at either baseline or follow-up examination (22.5±2.3 base pairs/y; P=0.79). At baseline, telomere length was associated with presence of carotid plaques (P=0.02) and with the number of regions with plaques (P=0.005). An interaction (P=0.03) between age and the presence of plaques was observed, such that the association between plaques and telomere length was more pronounced at a younger age. In conclusion, carotid atherosclerosis is not associated with increased telomere attrition during a 9.5-year follow-up period. Short telomere length is more strongly associated with early-onset than late-onset carotid atherosclerosis. Our results support the thesis that heightened telomere attrition during adult life might not explain the short telomeres observed in subjects with atherosclerotic disease. Rather, short telomeres antecedes the clinical manifestation of the disease.